Cognitive Impairment Before Atrial Fibrillation–Related Ischemic Events: Neuroimaging and Prognostic Associations. Issue 1 (7th January 2020) - Banerjee, Gargi; Chan, Edgar; Ambler, Gareth; Wilson, Duncan; Cipolotti, Lisa; Shakeshaft, Clare; Cohen, Hannah; Yousry, Tarek; Al‐Shahi Salman, Rustam; Lip, Gregory Y. H.; Muir, Keith W.; Brown, Martin M.; et al.
Abstract : Background: It is likely that a proportion of poststroke cognitive impairment is sometimes attributable to unidentified prestroke decline; prestroke cognitive function is also clinically relevant because it is associated with poor functional outcomes, including death. We investigated the radiological and prognostic associations of preexisting cognitive impairment in patients with ischemic stroke or transient ischemic attack associated with atrial fibrillation. Methods and Results: We included 1102 patients from the prospective multicenter observational CROMIS‐2 (Clinical Relevance of Microbleeds in Stroke 2) atrial fibrillation study. Preexisting cognitive impairment was identified using the 16‐item Informant Questionnaire for Cognitive Decline in the Elderly. Functional outcome was measured using the modified Rankin scale. Preexisting cognitive impairment was common (n=271; 24.6%). The presence of lacunes (odds ratio [OR], 1.50; 95% CI, 1.03–1.05; P =0.034), increasing periventricular white matter hyperintensity grade (per grade increase, OR, 1.38; 95% CI, 1.17–1.63; P <0.0001), deep white matter hyperintensity grade (per grade increase, OR, 1.26; 95% CI, 1.05–1.51; P =0.011), and medial temporal atrophy grade (per grade increase, OR, 1.61; 95% CI, 1.34–1.95; P <0.0001) were independently associated with preexisting cognitive impairment. Preexisting cognitive impairment was associated with poorer functional outcome at 24 months (mRS >2; adjusted OR, 2.43; 95% CI, 1.42–4.20; P =0.001). Conclusions: Preexisting cognitive impairment in patients with atrial fibrillation–associated ischemic stroke or transient ischemic attack is common, and associated with imaging markers of cerebral small vessel disease and neurodegeneration, as well as with longer‐term functional outcome. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02513316.